The Effect of Brand Image, Price, and Electronic Word of Mouth on Student Interest in Choosing a Private College in Bandung City (Study at Pasundan 2 Cimahi High School) - Sena, Muhamad Adryan Arya; Karamang, Ezra; Ali, Mochammad Mukti (International Journal of Marketing & Human Resource Research, 2025)
Instruction plays a critical part in the advancement of Indonesia, but there are still inequalities in higher education opportunities. This study looks at the effect of Brand Image, Cost, and Electronic Word of Mouth (e-WOM) on prospective students' interest in choosing a Private University (PTS) in Bandung City centred on Pasundan 2 Cimahi High School. This is done to analyze the effect of Brand Image, Cost, and e-WOM on interest in choosing PTS in Bandung City using a quantitative strategy with a purposive sampling method. Information was analyzed through validity, reliability, multiple linear regression, and F and T tests with an error rate of 5%. The results showed that Brand Image (X1) and e-WOM (X3) have a significant influence (p = 0.000 < xss=removed> 0.05). Thus, H1 and H3 are accepted, while H2 is rejected. This finding emphasizes that Brand Picture and e-WOM influence student interest, while Price has a smaller impact. This shows the importance of positive branding and computerized engagement for HEIs to remain competitive in attracting students. This research provides insights for educational institutions to develop strategies to address these factors and increase their attractiveness to prospective students amidst the increasingly fierce competition in higher education